Structure-based modeling of turnover of Bcl-2 family proteins bound to voltage-dependent anion channel 2 (VDAC2): Implications for the mechanisms of proapoptotic activation of Bak and Bax in vivo. (April 2020) - Dudko, Hanna V.; Urban, Viktar A.; Davidovskii, Alexander I.; Veresov, Valery G.
Graphical abstract: Highlights: Interactions of Bak, Bax and tBid with VDAC2 were modeled. The tBid > Bak > Bax hierarchy of binding affinities in respect to VDAC2 was revealed. Upon apoptosis induction, tBid displaces Bak from the VDAC2/Bak complex followed by the formation of the VDAC2/tBid complex. The VDAC2/tBid complex recruits Bax to the MOM upon apoptosis induction. VDAC2 helps Bak and Bax to insert their α9 helices into the MOM. Abstract: M itochondrial O uter M embrane (MOM) P ermeabilization (MOMP) is a critical event in the mitochondrial types of apoptosis. MOMP is controled by the proteins of the Bcl-2 family and its two proapoptotic members Bak and Bax are the key effectors of MOMP. Voltage-dependent anion channel 2 (VDAC2) is an integral membrane protein that plays an important role in the regulation of Bak and Bax apoptotic function, but underlying mechanisms are not fully understood. In the present article, the mechanisms of MOMP regulation mediated by VDAC2 were explored using structure-based modeling. We show that Bak, prior to an apoptotic stimulus, possesses two low-energy conformations of high shape – and polar complementarity in respect to VDAC2, resulting in two high-affinity modes of Bak binding to VDAC2, one with Bak fully residing in the cytosol and the other with Bak α9 helix inserted into the membrane. Even higher binding affinity of VDAC2 for tBid (truncated Bid/p15) was established, suggesting the tBid-mediated displacement of Bak from the VDAC2/Bak complex resulting in the formation of the VDAC2/tBid complex. The structural analysis of the interaction of this complex with Bax revealed a very high binding affinity of this complex for Bax, suggesting the recruitment of Bax to the MOM by this complex under apoptotic conditions. Besides, we revealed one more low-energy structure of Bax of high binding affinity towards the VDAC2/tBid complex and with helix α9 inserted into the membrane.